HLA Class I-Driven Evolution of Human Immunodeficiency Virus Type 1 Subtype C Proteome: immune Escape and Viral Load - Rousseau, Christine M.; Daniels, Marcus G.; Carlson, Jonathan M.; Kadie, Carl; Crawford, Hayley; Prendergast, Andrew; Matthews, Philippa; Payne, Rebecca; Rolland, Morgane; Raugi, Dana N.; Maust, Brandon S.; Learn, Gerald H.; et al. (Journal of Virology, 2008)
Human immunodeficiency virus type 1 (HIV-1) mutations that confer escape from cytotoxic T-lymphocyte (CTL) recognition can sometimes result in lower viral fitness. These mutations can then revert upon transmission to a new host in the absence of CTL-mediated immune selection pressure restricted by the HLA alleles of the prior host. To identify these potentially critical recognition points on the virus, we assessed HLA-driven viral evolution using three phylogenetic correction methods across full HIV-1 subtype C proteomes from a cohort of 261 South Africans and identified amino acids conferring either susceptibility or resistance to CTLs. A total of 558 CTL-susceptible and -resistant HLA-amino acid associations were identified and organized into 310 immunological sets (groups of individual associations related to a single HLA/epitope combination). Mutations away from seven susceptible residues, including four in Gag, were associated with lower plasma viral-RNA loads (q Gag > Rev > Pol > Nef > Vif > Tat > Env > Vpu (Fisher's exact test; P [≤] 0.0009 for each comparison), suggesting the same ranking of fitness costs by genes associated with CTL escape. Significantly more HLA-B (chi2; P=3.59 x 10-5) and HLA-C (chi2; P=4.71 x 10-6) alleles were associated with amino acid changes than HLA-A, highlighting their importance in driving viral evolution. In conclusion, specific HIV-1 residues (enriched in Vpr, Gag, and Rev) and HLA alleles (particularly B and C) confer susceptibility to the CTL response and are likely to be important in the development of vaccines targeted to decrease the viral load.